![](https://rs.olm.vn/images/avt/0.png?1311)
Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
![](https://rs.olm.vn/images/avt/0.png?1311)
![](https://rs.olm.vn/images/avt/0.png?1311)
a, 60.x/100-11.x/4=x+5
<=>60x/100- 275x/100 = (100x +500)/100
<=> 60x-275x=100x+500 ( khu mau)
<=> -315x=500
<=> x= - 100/63
b, 11x/2 -2x/3=54x/100
<=> 1650x/300-200x/300=162x/300
<=> 1650x - 200x =162x ( khu mau )
<=> 1450x=162x
<=> 1288x=0
<=> x=0
Mai thi tot nha !
![](https://rs.olm.vn/images/avt/0.png?1311)
a) 2.(x+1) - 3 = 11
2.(x+1) = 14
x + 1 = 7
x = 6
b) 60 - 5.(x-3) = 50
5.(x-3) = 10
x-3 = 2
x = 5
c) (10+2x).43 = 45
10 + 2x = 16
2x = 6
x =3
\(a,2\cdot\left(x+1\right)-3\left(11\right)=0.\)
\(\left(2\cdot\left(x+1\right)-3\right)-11=0.\)
\(2x-12=2\cdot\left(x-6\right)\)
\(2\cdot\left(x-6\right)=0.\)
\(x-6=0.\)
\(x=6.\)
\(b,\left(60-5\cdot\left(x-3\right)\right)-50=0\)
\(25-5x=-5\cdot\left(x-5\right)\)
\(-5x\left(x-5\right)=0.\)
\(x-5=0\)
\(x=5\)
Câu c khó quá bn tự làm nhé.
học tốt
![](https://rs.olm.vn/images/avt/0.png?1311)
![](https://rs.olm.vn/images/avt/0.png?1311)
-x + 5 + 2x = 4 - x
-1x + 5 + 2x = 4 - x
x( - 1 + 2 ) + 5 = 4 - x
x + 5 = 4 - x
=> x + 5 - 4 + x = 0
2x + ( 5 - 4 ) = 0
2x + 1 = 0
2x = 1
x = 1/2
![](https://rs.olm.vn/images/avt/0.png?1311)
\(\frac{4}{5}\)+ \(\frac{1}{5}\): \(\frac{-2}{15}\)= \(\frac{4}{5}\)+ \(\frac{1}{5}\)* \(\frac{-15}{2}\)=\(\frac{4}{5}\) + \(\frac{-3}{2}\)= \(\frac{-7}{10}\)
b = \(\frac{-7}{12}\). (\(\frac{3}{11}\)+ \(\frac{-14}{11}\)) + \(\frac{5}{6}\)= \(\frac{-7}{12}\). (-1) + \(\frac{5}{6}\)= \(\frac{7}{12}\)+ \(\frac{10}{12}\)= \(\frac{17}{12}\)
![](https://rs.olm.vn/images/avt/0.png?1311)
\(a.\frac{8}{7}+\frac{4}{7}\times\left(-\frac{6}{11}\right)-\frac{4}{7}\times\frac{5}{11}\)
\(=\frac{8}{7}+\frac{4}{7}\left(-\frac{6}{11}-\frac{5}{11}\right)\)
\(=\frac{8}{7}+\frac{4}{7}.\left(-1\right)\)
\(=\frac{8}{7}-\frac{4}{7}\)
\(=\frac{4}{7}\)
![](https://rs.olm.vn/images/avt/0.png?1311)
a. (x2 - 4).(x+3/5) = 0
TH1: x2 - 4 = 0
x2 = 4
x2 = 22
-22
=> x = 2
-2
Vậy x \(\in\){-2;2}
x - 5 = ( -11) + (-4)
x - 5 = (-15)
x = (-15) + 5
x = (-10)
lxl = 2
=> x = -2 ; x = 2
x - 5 = (-11) + (-4)
=> x - 5 = (-15)
=> x = (-15) + 5
=> x = -10
Vậy x = -10